ETOS KERJA DALAM EKONOMI GLOBAL (KASUS MASYARAKAT MUSLIM MELAYU PALEMBANG) - Ritawati, Raden Ayu (Nurani, 2018)
The purpose of this research is to know the influence of Malay and Islam in shaping the social character of Palembang Malay workers in global economic development. The Islamic economic norms embedded and rooted in the local social identity of the local Malays are the key determinants of evaluative aspects of a judging nature. This research departs from the reason as Ushul Fiqih's written adage says "Al-Muhafazhatu'alal 'qadimis salih wal-akhdzu bil jadidil ashlah" which means "Maintaining a good old value and seeking new value better.” Field research with the participation of observations and in-depth interviews uses a qualitative approach. Respondents in this study are Palembang original Malay Muslim community, spread over 14 districts using random sampling technique. While the method of data analysis is cyclical of three stages: data collection, data display and data verification. The results of this study prove that excessive material competition in the global economy has resulted in an anomic Palembang Malay society. Achievements in the economic field, it turns out to have transformed Palembang Malay people into a generation that is uprooted from values, fragile from the spiritual aspect, give up easily and lose socio-economic footing. The relationship of Malayness and Islamism obscures the role and competitiveness of Palembang Malay Muslims themselves in the global economic arena.